2013
DOI: 10.3109/19396368.2013.864343
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status shifts in uterine cervical incompetence patients

Abstract: Uterine cervical incompetence (UCI) is a pregnancy complication affecting about 10% of the pregnancies in the western world. Studying the etiology of the UCI requires a specific approach adequate for this highly heterogenous syndrome. Oxidative status disorders are associated with various pathologies, including pregnancy complications. As such, general oxidative status profiling is a promising methodology to treat UCI. We aimed at assaying the closely interrelated oxidative status markers in the uterine cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The underlying mechanisms leading to spontaneous preterm labour are not fully understood. Evidence for oxidative stress in women with cervical incompetence is inconsistent, 40 and this may reflect the heterogeneous nature of this population. Another study has reported significantly decreased serum selenium concentrations in women who went on to deliver preterm compared to controls.…”
Section: Preterm Labour and Preterm Pre-labour Rupture Of Membranesmentioning
confidence: 99%
“…The underlying mechanisms leading to spontaneous preterm labour are not fully understood. Evidence for oxidative stress in women with cervical incompetence is inconsistent, 40 and this may reflect the heterogeneous nature of this population. Another study has reported significantly decreased serum selenium concentrations in women who went on to deliver preterm compared to controls.…”
Section: Preterm Labour and Preterm Pre-labour Rupture Of Membranesmentioning
confidence: 99%
“…Clinical and experimental evidence suggests that uric acid plays a major role in the human body as an antioxidant and OS marker (38). Studies on the etiopathogenesis of abortion have not yet measured serum uric acid level as a biomarker of OS; however, the marker has been measured in some pregnancy complications such as cervical insufficiency (39) and preeclampsia (40).…”
Section: Discussionmentioning
confidence: 99%
“…Our lab developed an NFE2L2/ AP-1 pathway-based systemic biomarker for assessing slight changes in physiological parameters of the human organism using peripheral blood leukocytes as the preferred sample type [66]. The same systemic approach utilizing another set of oxidative status markers was successfully used for unveiling features of uterine cervical incompetence patients [67]. Other labs also successfully apply pathway activation-based technologies in various field and other sample types, with special attention paid to fresh solid tumors samples and paraffin blocks [68].…”
Section: Current Advances In Developing Systemic Biomarkersmentioning
confidence: 99%